EXPLORING ASNAF PERCEPTIONS OF QR CODE AND NFC PAYMENTS: AN EMPIRICAL STUDY - Badrul Hisham Abd Rahman; Nor Izham Subri; Abdul Ghafur Hanafi (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2024)
Emerging technology, such as QR Code and NFC payment gateway, exemplified by services like Maybank’s MAE and Touch ’n Go NFC, is transforming the landscape of digital financial transactions. This empirical research, titled "Exploring Asnaf Perceptions of QR Code and NFC Payments: An Empirical Study," delves into the attitudes and experiences of Asnaf beneficiaries regarding the adoption and utilization of these innovative payment methods within the context of fintech and Asnaf management. Employing a user-centric approach and employing qualitative data analysis through thematic analysis, the research aims to gain a comprehensive understanding of Asnaf beneficiaries’ perspectives. The study encompasses a comprehensive review of pertinent literature, underscoring the significance of fintech in Asnaf management, and delineating the theoretical framework. Qualitative research methods, including semi-structured interviews and focus groups with selected Asnaf beneficiaries, are used to extract and interpret recurring themes in the qualitative data. The results of the analysis provide valuable insights into Asnaf beneficiaries’ perceptions and preferences concerning QR Code and NFC payments. The findings of this study have considerable implications for enhancing Asnaf management and guiding fintech strategies to better meet the unique needs and preferences of Asnaf beneficiaries in the digital era. Moreover, the research underscores the importance of incorporating a user-centric approach in fintech studies and demonstrates the effectiveness of thematic analysis as a qualitative research method.